Etika Ritual Pada Pemujaan di Pura Sari Desa Selat Pandan Banten, Kecamatan Sukasada Kabupaten Buleleng - Somawati, Ayu Veronika; Hartaka, I Made; Yuliani Dewi, Ni Luh Putu (Jayapangus Press, 2024)
Buleleng Regency has many old and unique temples which are very interesting to study. One of them is Sari Temple in Selat Pandan Banten Village, Sukasada District. In addition to the unique shape of the building, this temple also has a ritual ethic that distinguishes it from temples in general. The purpose of writing this article is to examine the forms and values ​​of ritual ethics in this temple. By using the methods of observation, interviews and documentation studies, the authors examine the existence of Sari Temple and the ritual ethics of the temple. Based on research results, the sacred building at Sari Temple is still in the form of bebaturan which has been maintained until now. The community agreed to maintain the original form of the temple because apart from preservation purposes, it is also because of the community's belief that has been passed down from generation to generation to always maintain the originality of the temple. Apart from being related to the shape of the building, this temple also has ritual ethics, that are worship is carried out without using bells, not using gongs and performing dances in the main area of ​​the temple and not being allowed to offer four-legged animals (suku pat). All of this is a form of implementation of religious teachings and the people's efforts to continue to carry out the traditions from generation to generation.